TEACHERS' EXPERIENCES AND PERCEPTIONS OF INCLUSION OF STUDENTS WITH INVISIBLE DISABILITIES IN SCHOOLS IN KAZAKHSTAN - Tergeussizova, Zhulduz (Nazarbayev University Graduate School of Education, 2024)
ABSTRACT Teachers' Experiences and Perceptions of Inclusion of Students with Invisible Disabilities in Schools in Kazakhstan Inclusive education is a fundamental principle of the Convention on the Rights of Persons with Disabilities (CRPD), emphasizing the right of all students to equitable quality education. Yet, the successful inclusion of students with invisible disabilities remains a complex issue within Kazakhstan schools. Therefore, this study investigates teachers' experiences and perceptions regarding the inclusion of students with invisible disabilities, exploring their conceptualizations of invisible disabilities, experiences in addressing students' needs, and the enablers and challenges they encounter. Employing a qualitative research design informed by Vygotsky theory utilized semi-structured interviews with teachers from a mainstream school in Astana, Kazakhstan. Data was analysed thematically. Key findings indicate that even experienced teachers may lack understandings of invisible disabilities. Teacher attitudes toward inclusion varied, with some demonstrating positivity, others negativity, and a portion remaining neutral. Challenges stem from limited formal documentation of disabilities and parental reluctance to disclose them. Teachers expressed a strong desire for practical training and courses focusing on teaching students with invisible disabilities. Additionally, they emphasized the critical need for support from school leadership. This study's insights have implications for policy, practice, and research. Findings underscore the need for targeted training, professional development, and robust teacher support systems. In practice, greater awareness of invisible disabilities among teachers is essential for improving inclusive educational quality and student outcomes. Further research should explore perspectives in rural areas, as this study focused on an urban setting. By strategically addressing these challenges, policymakers, educators, and communities can work together to advance inclusive education practices in Kazakhstan and beyond, ensuring that every student, regardless of background, has the equal opportunity and support to thrive in education. Keywords: inclusive education, invisible disabilities, Kazakhstan, perceptions and experience of teachers, qualitative research, teachers, Vygotsky theory.
Keywords: Type of access: Open Access; inclusive education; invisible disabilities; Kazakhstan; perceptions and experience of teachers; qualitative research; teachers; Vygotsky theory